‘A Vast Speculation’:The Cork Grand Musical Meeting of 1826 - O’Regan, Susan (Journal of the Society for Musicology in Ireland, 2010)
The organization of a Grand Musical Meeting in Cork in 1826 was the biggest commercial undertaking in the city’s concert life up to that time, bringing from London four virtuoso instrumentalists and at least six solo singers, in addition to a choir and orchestra. The event was directed by William Forde, a Cork-born musician who had for some years worked as a professional musician in London. The lavish plans for six concerts, an oratorio and an opera were not brought to fruition, and, by the fifth day, events were necessarily curtailed due to poor audience attendance. The scale of the event, its mismatch with the intended audience and a clash with the city’s annual theatre season all contributed to the difficulties which the organisers encountered, although artistic integrity and strong press support were in evidence. The publicity notices for the Grand Musical Meeting also reveal links with London’s newly-established Royal Academy of Music. This article examines the circumstances surrounding the event and questions its unstated aims.